Pendampingan Praktik Percetakan Modern untuk Meningkatkan Daya Saing Lulusan Program Keahlian Grafika SMKN 2 Peusangan - Satria M, Deddy; Andyna, Cut; Denny Sumantri Mangkuwinata; Muhammad Diah (Universitas Malikussaleh, 2025)
This community service activity aims to improve the quality and selling value of processed corn products through the use of digital technology in marketing to the community in Sawang District. In the era of digital economy, digital literacy skills are the key to increasing the competitiveness of local products. However, most businesses and farmers in this region still face obstacles such as low understanding of digital marketing, limited access to technology, and lack of skills in producing promotional content. This training program is designed to answer these challenges by providing practical materials about digital marketing, such as the use of social media, graphic design, product photography, SEO, and the use of e-commerce platforms. The results of the training showed a significant improvement in product quality, participants' digital skills, and micro and small business income. In addition, this activity also encourages the formation of local business networks and changes in the mindset of MSME actors to be more adaptive to technological developments. The sustainability of the program is expected through further assistance and synergy between related parties.